2018
DOI: 10.1097/md.0000000000012659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liuzijue Qigong on patients with chronic obstructive pulmonary disease

Abstract: Background:Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide with a substantial and increasing social and economic burden. Liuzijue Qigong is a kind of traditional Chinese Qigong exercises that Traditional Chinese Medicine practitioners prescribe to individuals with COPD to strengthen the internal organs’ function. Liuzijue Qigong was recommended for use in COPD rehabilitation, and some clinical trials indicate that Liuzijue Qigong would produce better functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…23 Qigong exercise comprises abdominal breathing and pursed-lip breathing, which can slow the breathing rate and improve the patient's breathing difficulties. 19 During the pronunciation of the 6 different sounds, the corresponding movement of the upper limbs not only increases the volume of the chest cavity and deepens breathing 24 but may also help to loosen the adhesion of mucus to the epithelium of the respiratory tract. In addition, many studies have shown that applying pressure on acupoints related to the lungs helps improve dyspnea.…”
Section: Potential Mechanism Of Actionmentioning
confidence: 99%
“…23 Qigong exercise comprises abdominal breathing and pursed-lip breathing, which can slow the breathing rate and improve the patient's breathing difficulties. 19 During the pronunciation of the 6 different sounds, the corresponding movement of the upper limbs not only increases the volume of the chest cavity and deepens breathing 24 but may also help to loosen the adhesion of mucus to the epithelium of the respiratory tract. In addition, many studies have shown that applying pressure on acupoints related to the lungs helps improve dyspnea.…”
Section: Potential Mechanism Of Actionmentioning
confidence: 99%
“…TCEs are regarded as a form of mind-body intervention for the treatment of various chronic diseases. [ 8 ] Among the TCEs, Liuzijue, one of the New Health Exercise Series compiled by the China Qigong Management Center, is the most popular exercise in ancient Chinese literature. [ 9 , 10 ] Liuzijue involves inhalation and exhalation through different mouth patterns to regulate and control the rise and fall of the breath in the body.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Liuzijue Qigong is featured by diaphragmatic breathing and pursed-lip breathing can make COPD patients breathing rate slowly and prevent the premature airway occlusion caused by rapid airflow to improve the abnormal breathing pattern of patients. [26] It is helpful for the function of the auxiliary breathing muscles and enhances the flexibility, coordination, and control capacity on neuromuscular limbs to further improve exercise capacity in patients with COPD. [27]…”
Section: Discussionmentioning
confidence: 99%